CHIP protects lysosomes from CLN4 mutant-induced membrane damage. - Lee, J.; Chin, N.; Zou, J.; Mazli, W.N.A.B.; Jarnik, M.; Saidi, L.; Xu, Y.; Jeong, E.; Suh, J.; Replogle, J.; Ward, M.E.; Bonifacino, J.S.; et al. (Nature Cell Biology, 2025)
Understanding how cells mitigate lysosomal damage is critical for unravelling pathogenic mechanisms of lysosome-related diseases. Here we generate and characterize induced pluripotent stem cell (iPSC)-derived neurons (i[3]Neuron) bearing ceroid lipofuscinosis neuronal 4 (CLN4)-linked DNAJC5 mutations, which revealed extensive lysosomal abnormality in mutant neurons. In vitro membrane-damaging experiments establish lysosomal damages caused by lysosome-associated CLN4 mutant aggregates, as a critical pathogenic linchpin in CLN4-associated neurodegeneration. Intriguingly, in non-neuronal cells, a ubiquitin-dependent microautophagy mechanism downregulates CLN4 aggregates to counteract CLN4-associated lysotoxicity. Genome-wide CRISPR screens identify the ubiquitin ligase carboxyl terminus of Hsc70-interacting protein (CHIP) as a central microautophagy regulator that confers ubiquitin-dependent lysosome protection. Importantly, CHIP's lysosome protection function is transferrable: ectopic CHIP improves lysosomal function in CLN4 i[3]Neurons and effectively alleviates lipofuscin accumulation and cell death in a Drosophila CLN4 disease model. Our study establishes CHIP-mediated microautophagy as a key organelle guardian that preserves lysosome integrity, offering new insights into therapeutic development for lysosome-related neurodegenerative diseases.